Optimal Probe Length and Target Location for Electrochemical Detection of Selected Uropathogens at Ambient Temperature - Mastali, Mitra (American Society for Microbiology (ASM), 2008)
We have previously demonstrated the clinical validity of the rapid detection of uropathogens by use of a DNA biosensor. This assay involves the hybridization of capture and detector probe pairs with bacterial 16S rRNA target molecules to form a DNA-RNA sandwich on the sensor surface. Horseradish peroxidase-conjugated antibody binds to the detector probe to enzymatically amplify the hybridization signal. These previous studies involved the hybridization of bacterial 16S rRNA target sequences with 35-mer oligonucleotide probe pairs at 65°C. Achievement of point-of-care technology will be greatly facilitated by ambient-temperature detection. The purpose of this study was to examine the effects of probe length and target location on signal intensity using hybridization temperatures of 20 to 25°C. Signal intensity was found to vary dramatically with hybridization location in the species-specific bulge region of 16S rRNA helix 18. Probe pairs of as short as 10 nucleotides in length were able to produce a significant electrochemical signal, and signal intensity was correlated with probe length for probes of 10 to 20 nucleotides in length. The sensitivity of the Escherichia coli-specific 15-mer probe pairs was approximately 330 cells. These shorter probes allowed differentiation of Klebsiella pneumoniae from Proteus mirabilis 16S rRNA target sequences differing by a single nucleotide. A panel of oligonucleotide probe pairs ranging from 11 to 23 nucleotides in length was able to distinguish among seven groups of urinary tract pathogens. In conclusion, we have developed short oligonucleotide probe pairs for the species-specific identification of uropathogens at ambient temperature by use of an electrochemical sensor.